Batch and column studies on biosorption and desorption of nickel on mustard oil cake - Ngabura, Mohammed (2012)
Discharge of industrial effluents such as electroplating of Malaysia that contains heavy metals into water bodies could results in deteriorating drinking and ground water quality. The heavy metals are non-biodegradable and show detrimental effect on flora and fauna as well as eco-system. Beyond permissible limit, toxicity of nickel was listed in this thesis. A series of batch and column laboratory studies were conducted in other to investigate the biosorption potentials of mustard oil cake (MOC). This biomass was used for minimization of Ni(II) ions from aqueous medium under different experimental conditions. This research is based on synthetic solution prepared in the laboratory. Parameters such as pH, temperature, contact time, initial nickel concentration, biosorbent dose, particle size of biosorbent and agitation speed indicated a greater influence in the biosorption process. The optimum biosorption was observed at pH 8. The biosorption increases from 0.869 to 0.915 mg/g with increase in temperature from 303 to 323 K at pH 8. Biosorbent dose studies showed increase in biosorption from 59.4 to 78.4% with increase in biosorbent dose from 0.05 to 1 g. The contact time studies revealed an equilibration time between 240 to 720 min. Adsorbate concentration studies showed an increase in biosorption capacity with increase in reaction temperature and concentration. Spectroscopic studies indicated possible involvement of acidic (hydroxyl, carbonyl and carboxyl) groups in biosorption process. Langmuir, Freundlich and Temkin models were applied to the biosorption data. The results fitted Freundlich isotherm model which possessed high correlation coefficient (R2) value compared to other two models. Freundlich constant (n) and activation energy (Ea) values confirmed physical nature of the process. Kinetics studies revealed applicability of Pseudo-second-order model. Thermodynamic parameters indicated that the process is endothermic and spontaneous in nature. The breakthrough and exhaustive capacities for 5 mg/L initial Ni(II) concentration were 0.25 and 4.5 mg/g, while for 10 mg/L initial Ni(II) concentration were 4.5 and 9.5 mg/g, respectively. Batch desorption studies showed 99.4 to 99.8% Ni(II) recovery with HCl solution in single-metal system. Column desorption studies were carried out at 5 and 10 mg/L initial Ni(II) concentration in single metal system. Results showed 82 and 84% of Ni(II) was recovered in initial 10 mL eluent for 5 and 10 mg/L initial Ni(II) concentrations, respectively. Regeneration studies by batch and column process confirmed reutilization of biomass without appreciable loss in biosorption. Finally, mustard oil cake was found to be cost effective and has considerable efficiency of minimizing nickel ion from aqueous solution to permissible limit.